Implementación de un módulo didáctico de instalaciones eléctricas residenciales para el laboratorio de la carrera de Ingeniería Electromecánica de la Universidad Técnica de Cotopaxi Extensión La Maná. - Piñaloza Castro, Luis Andres (2022)
The didactic modules have proven to be an effective instrument in the training of professionals in different fields of study. With the inclusion of a tool, the full training of people in the course of their academic life was guaranteed, which leads the student to polish their correct professional profile. Through the observation of the Electromechanics laboratory at Universidad Técnica de Cotopaxi in La Maná, it was verified the lack of adequate resources that would ensure the optimal equipment. This limited the teachers' ability to impart their practical knowledge in an adequate manner to the students. The didactic module of residential electrical installations aims to improve and enhance the laboratory through the implementation of the same. In carrying out this project, the experimental method was used to study the work and application of the different devices used for the development of low voltage electrical circuits for residential complexes. Simultaneously, with the calculations of the electrical variables found in them. In this way, several practical activities were obtained as a result, which provides the module's operation capacity. Allowing more people are integrated to develop their technical skills and qualities that are obtained at the same time in different sections of simulation. Through the execution of the project, students are favored in their theoretical and practical training. It promotes the enhancement and development of the career and extension as an axis of quality and excellence promoting a broad technological knowledge demonstrating higher level skills with current standards of efficiency, quality, and student safety in this field.